HIV status and knowledge of cervical cancer among women in Ghana - Nancy Innocentia Ebu Enyan; Sebastian Ken-Amoah; Derek Anamaale Tuoyire; Kafui Patrick Akakpo; Elizabeth Agyare; Dorcas Obiri-Yeboah (BMC, 2024)
Abstract Background Cervical cancer remains a disease of significant concern to women's health. The aim of this study was to identify predictors of knowledge of cervical cancer among women living with HIV and those with negative or unknown HIV status at the Cape Coast Teaching Hospital (CCTH). Methods This study was based on a larger hospital-based analytical cross-sectional study conducted at the antiretroviral therapy (ART) and gynaecology clinics of the Cape Coast Teaching Hospital in Ghana. Participants were women living with HIV (WLHIV) and women without HIV or whose status was unknown, aged 25 to 65 years, seeking healthcare. Data were collected with a questionnaire and analysed using frequencies, percentages, Chi-square test, binary logistic regression and multivariate analysis. Results The mean age was 39.5 years (± 9.8) and 47.2 years (± 10.7) for women without or unknown HIV and WLHIV, respectively. HIV-negative/unknown women were mostly nulligravida (76%) and nullipara (69%), while WLHIV mostly had pregnancies (76%) and children (84%) in excess of seven. Knowledge of cervical cancer was statistically significantly associated with HIV status (X2 = 75.65; P-value = 0.001). The odds of having knowledge of cervical cancer for women considered to be negative/unknown for HIV were about three times (AOR = 3.07; 95% CI = 1.47, 6.41) higher than their compatriots with HIV. Women with post-secondary/tertiary (AOR = 4.45; 95% CI = 2.11, 9.35) education had significantly higher odds of having knowledge of cervical cancer than those with no education or those with just primary education. Conclusions To improve knowledge of cervical cancer among women, an intentionally structured health education programme is needed, particularly for WLHIV, those with lower levels of education and the unemployed.